Pertumbuhan tanaman pakcoy (Brassica rapa subsp. chinensis) sistem vertikultur dengan fertigasi di lahan kering: Pakcoy (Brassica rapa subsp. Chinensis) Growth in Verticulture System with Fertigation on Dry Land - Neonbeni, Eduardus Yosef; Tobing, Wilda Lumban; Gumelar, Asep Ikhsan; Tuas, Maria Angelina; Sabuna, Rolinus (AGROMIX, 2022)
Introduction: This study aimed to determine the growth of pakcoy at the time of fertigation and the composition of the verticulture system planting media with different spacing of planting holes and their interactions on dry land. Methods: The method used is an experiment using a Split Plot Design using 3 plots. The main plot is the spacing of the planting holes consisting of 15 cm, 20 cm, and 25 cm. The subplot is the composition of the growing media consisting of soil:sand, soil:biochar; sand:biochar; and soil:sand:biochar. The sub-sub plot is fertigation time which consists of 60 seconds, 90 seconds, and 120 seconds. A total of 36 treatments were repeated 2 times for a total of 72 treatments. Results: Results: The results of this study showed that the interaction of fertigation time significantly affected the growth of plant height, number of leaves and fresh weight of crown with the best combination treatment of 120 seconds of fertigation time with soil:biochar growing media. Fertigation time has a significant effect on all observation parameters, with the best treatment being fertigation for 120 seconds. The composition of the growing media had a significant effect on the observations of plant height, the number of leaves, and the fresh weight of the crown with the best results found in soil: biochar growing media (1:1). Conclusion: The best combination result is a fermentation time of 120 seconds and the composition of soil and biochar (W3M2).